L1′ ordering: Evidence of L10–L12 hybridization in strained Fe38.5Pd61.5 epitaxial films. (15th February 2015) - Steiner, Matthew A.; Comes, Ryan B.; Floro, Jerrold A.; Soffa, William A.; Fitz-Gerald, James M.
Abstract: The existence of an L10 –L12 hybrid ordered phase for face-centered cubic (fcc) crystal symmetry was first theorized by William Shockley in 1938, but has not been verifiably observed to date. Ordered magnetic thin films of Fe38.5 Pd61.5, the expected L10 –L12 eutectoid composition, grown epitaxially on MgO(0 0 1) substrates by pulsed laser deposition, are shown to exhibit the first empirical confirmation of L1′ type ordering. A formal treatment of L1′ ordering requiring the definition of two independent ordering parameters is discussed in conjunction with the crystallographic and magnetic characterization of the Fe38.5 Pd61.5 thin films. Two theories regarding origination of the unique metastable ordering behavior induced by the non-equilibrium strain conditions are proposed.